FAT1 mutation-related signature predicts survival risk and tumor immunogenicity in lung adenocarcinoma - Gao, Lifeng; Wang, Xueying; Xu, Yixin; Wang, Aimin; Zhang, Wenjing; Wang, Qinghua; Ren, Yanfeng (Frontiers in Genetics, 2025)
BackgroundFAT atypical cadherin 1 (FAT1) is a well-known tumor regulator that plays a crucial role in multiple cancer signaling pathways. Its mutations have been linked to tumor progression and immune regulation in various cancers, including lung adenocarcinoma (LUAD). In this study, we aim to identify a FAT1 mutation-related transcriptomic risk signature to assess the survival risks and immune status of LUAD patients.MethodsA total of 2528 LUAD samples, which included both gene expression profiles and clinicopathologic data, were collected from 12 datasets. Additionally, two datasets treated with immunotherapies were also included to investigate the therapeutic effects.ResultsWe constructed a FAT1 mutation molecular signature based on 9 relevant genes. LUAD patients with low-risk scores demonstrated a more favorable prognosis compared to those with high-risk scores, which is corroborated by 6 additional independent datasets. Further immunological, mutational, and intratumor microbial analyses reveal that increased infiltration of immune effector cells, increased mutational burden, specific mutational signatures (such as age and APOBEC associated), mutations in driver genes (e.g., TP53, KEAP1, NAV3, and SMARCA4), and increased microbial α/β diversities are present in the low-risk LUAD patients. Based on the immunotherapeutic patients, an improved immune checkpoint blockade treatment prognosis and an elevated response rate are also observed in the low-risk signature group.ConclusionIn summary, Our identified FAT1 mutation-related risk signature shows potential for assessing LUAD clinical outcomes, tumor immunogenicity, and immunotherapy effectiveness, providing valuable insights for LUAD clinical practice.